WASTE DISPOSAL SYSTEM FOR SMALL GROUPS AT REMOTE USAF SITES IN THE ARCTIC - Walters,C. F.; Baumgartner,D. J. (1963)
A waste disposal system for two people incorporating a marine toilet, chlorinator and storage tank was designed and investigated by the Arctic Health Research Center to provide a recirculating liquid for toilet flushing, thus eliminating the need for fresh water. The system is not intended to allow biological or chemical breakdown of the organic waste, but merely to provide an acceptable method of waste storage. Ultimate disposal is required. It is anticipated that this system will provide a method of waste disposal for small groups of men assigned to remote radar sites in Alaska. The experimental unit proved acceptable for a two-member household for a trial period of five months. The system possesses the following characteristics: (1) minimum water use, (2) minimum energy use, (3) not subject to or rendered unusable by freezing, (4) minimum problem of ultimate disposal, (5) minimum odors, (6) minimum maintenance and (7) conventional toilet. (Author)